Star-planet connection through metallicity. Issue 67 (17th July 2015) - Adibekyan, V.Zh.; Figueira, P.; Santos, N.C.; Israelian, G.; Mortier, A.; Mordasini, C.; Delgado Mena, E.; Sousa, S.G.; Correi, A.C.M.; Oshagh, M.
Abstract : We used a large sample of FGK dwarf planet-hosting stars with stellar parameters derived in a homogeneous way from the SWEET-Cat database (Santos et al. 2013) to study the relation between stellar metallicity and position of planets in the period-mass diagram. Using this large sample we show that planets orbiting metal-poor stars have longer periods than those in metal-rich systems. This trend is valid for masses at least from ≈ 10  M ⊕ to ≈ 4  M Jup . Moreover, Earth-like planets orbiting metal-rich stars always show shorter periods (≤20 days) than those orbiting metal-poor stars. However, in the short-period regime there are a similar number of planets orbiting metal-poor stars. Our results suggest that the planets in the P-M P diagram are evolving differently because of a mechanism that operates over a wide range of planetary masses. This mechanism is stronger or weaker depending on the metallicity of the respective system. Most probably planets in metal-poor disks form farther out from their central star and/or they form later and do not have time to migrate as far as the planets in metal-rich systems.